2012
DOI: 10.1002/dmrr.1219
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and complications associated with type 2 diabetes in migrant South Asians

Abstract: It is estimated that type 2 diabetes (T2D) currently affects about 246 million people worldwide, with South Asians, especially Indians, having both the largest number of cases and the fastest growing prevalence. South Asian ethnicity has been identified as a major risk factor for the development of T2D with central adiposity, insulin resistance and an unfavourable lipid profile being identified as predominant signals of alarm. Leading databases, including Web of Science, Medline, PubMed and Science Direct, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 151 publications
(173 reference statements)
2
45
0
2
Order By: Relevance
“…However, as immigrants increase their exposure to Western cultural practices, they may adopt less healthy food choices found in their host country (Akresh, 2007;Batis et al, 2011;Guendelman et al, 2011;Kim et al, 2007;Lv and Cason, 2004). For Asian Indians, this may mean reduced intake of plant foods or altered meal patterns that may increase risk for overweight/obesity and obesity-related conditions (Garduno-Diaz and Khokhar, 2012;Garduño-Diaz and Khokhar, 2012;Karim et al, 1986;Raj et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, as immigrants increase their exposure to Western cultural practices, they may adopt less healthy food choices found in their host country (Akresh, 2007;Batis et al, 2011;Guendelman et al, 2011;Kim et al, 2007;Lv and Cason, 2004). For Asian Indians, this may mean reduced intake of plant foods or altered meal patterns that may increase risk for overweight/obesity and obesity-related conditions (Garduno-Diaz and Khokhar, 2012;Garduño-Diaz and Khokhar, 2012;Karim et al, 1986;Raj et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…1 School of Food Science and Nutrition, University of Leeds, Leeds, LS2 9JT, UK South Asians represent the largest ethnic minority group in the UK and have been reported to have greater risk of chronic diseases compared with Caucasians (1) . South Asians also experience the double burden of malnutrition, and also presenting deficiencies as well as over-nutrition (2) .…”
mentioning
confidence: 99%
“…Various studies have reported a number of dietary imbalances in South Asian diets associated with IR, such as high intake of total fat, saturated fatty acids, long chain u-6 polyunsaturated fatty acids (PUFA), trans fatty acids, and carbohydrates, and low intake of monounsaturated fatty acids, long chain u-3 PUFAs, fiber, and several micronutrients (e.g. magnesium, calcium, and vitamin D) (68,69,70,71,72,73). Furthermore, children and adolescents already have a high intake of u-6 PUFA and a low intake of u-3 PUFA, which is correlated with fasting hyperinsulinemia (74,75).…”
Section: Diet and Exercisementioning
confidence: 99%